Digitalisasi Akuntansi di Era Industri 4.0: Systematic Literature Review Atas Tren, Manfaat, dan Tantangan (2018–2025) - Winda Wulandari; Heksawan Rahmadi; Retna Sari; Sumardi Sumardi; Wieldy Menanda (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to systematically map the evolution of accounting digitalization through a Systematic Literature Review (SLR) approach. The review analyzed 30 peer-reviewed articles published between 2018 and 2025 comprising 20 Scopus-indexed international and 10 SINTA-indexed national journals, sourced from Scopus, ScienceDirect, Emerald Insight, Google Scholar, and SINTA databases. The analysis identified five dominant research themes: big data analytics, artificial intelligence (AI), blockchain, cloud-based accounting, and socio-institutional dimensions. Among these, AI and big data emerged as the most prominent topics, reflecting a technological shift in accounting practices. The findings demonstrate that accounting digitalization not only enhances efficiency and transparency but also transforms the accountant’s role and regulatory landscape. This study contributes by synthesizing research trends, identifying thematic gaps, and proposing a future research agenda to strengthen the digital transformation of accounting in the Industry 4.0 era